2019
DOI: 10.3390/ijerph17010198
|View full text |Cite
|
Sign up to set email alerts
|

“There’s Not Really Much Consideration Given to the Effect of the Climate on NCDs”—Exploration of Knowledge and Attitudes of Health Professionals on a Climate Change-NCD Connection in Barbados

Abstract: Despite widespread awareness of the rise of non-communicable diseases (NCDs) and the growing threat of climate change, little research has explored future health outcomes that will occur at the intersection of these challenges. Ten Barbadian health professionals were interviewed to assess their knowledge of health risks of climate change as it relates to NCDs in Barbados as a case study of a small island state at risk. There is widespread concern among health professionals about the current and future prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Although in the strict medical viewpoint, NCDs are non-transmissible between individuals. However, owing to the deep-rooted linkages NCDs share with geographical and behavioral aspects, like temperature, altitude, precipitation, pollution levels, dietary influences, lifestyle modifications, exposure to risky health behaviors, non-compliance with medical regimes and avoidance towards health care [34]; it would not be an exaggeration to affirm that, each individual has the tendency and capacity to alter the behaviors of another individual, living in the vicinity; which, can be referred to as "neighborhood affect".…”
Section: Implications Of Findingsmentioning
confidence: 99%
“…Although in the strict medical viewpoint, NCDs are non-transmissible between individuals. However, owing to the deep-rooted linkages NCDs share with geographical and behavioral aspects, like temperature, altitude, precipitation, pollution levels, dietary influences, lifestyle modifications, exposure to risky health behaviors, non-compliance with medical regimes and avoidance towards health care [34]; it would not be an exaggeration to affirm that, each individual has the tendency and capacity to alter the behaviors of another individual, living in the vicinity; which, can be referred to as "neighborhood affect".…”
Section: Implications Of Findingsmentioning
confidence: 99%
“…Semi-structured questionnaires with open-ended and probing questions were used for the FGDs and IDIs. To ensure validity, the questionnaire guides were constructed congruently with the specific research questions based on guides from similar studies identified by a thorough literature review, and modified to the Kenyan context [6,17,18]. The questionnaires were developed in English, evaluated by two independent researchers (Johanne Greibe Andersen and Christian Kraef) in addition, NCDAK evaluated and pilot tested the tools to confirm their validity.…”
Section: Data Collectionmentioning
confidence: 99%
“…Furthermore, their effects are felt in every sector, including health, agriculture, infrastructure, and education [ 8 ]. This research is part of a larger research program investigating the relationships between health, inequalities, and wellbeing in low/middle-income countries [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%